Memorialising queer community: digital media, subjectivity and the Lost Gay # archives of social networking. Issue 1 (February 2019) - Cover, Rob
Following the development of online sites dedicated to the preservation of individuals' photographic and textual memorialisation of cities, a number of archiving sites using Facebook have been developed that cater to the interactive and co-creative practice of memorialising LGBTQ (lesbian, gay, bisexual, transgender and queer) city-based communities, events and public spaces (e.g. Lost Gay Perth and Lost Gay Melbourne). Such minority community practices of memorialisation invoke deeply felt and affective attachments to 'past' in ways which have implications for identity, belonging, ageing and agency. This article utilises a critical approach to archiving, temporality, identity and attachment to interrogate some of the ways in which digital cultural practices related to archiving social networking sites are implicated in the memorialisation of community belonging through notions of past, networks of knowing, and the temporal and historical production of ways of thinking about and knowing minority sexuality, particularly LGBTQ subjectivity.